GLOBAL COOLER ROOF (GCR): KONSEP BANGUNAN PENGOLAH EMISI KENDARAAN BERMOTOR SEBAGAI SALAH SATU SOLUSI GLOBAL WARMING - Alkhabib, Akhmad; Sarassantika, I Putu Ellsa; Manudianto, Dedy; Julia, Chiendy Fajjaraini Ratna (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The concept of building a traffic light as a complement to the processing vehicle emissions causes global warming called âGlobal Cooler Roof (GCR)â. GCR shaped like a roof over the road consisting of two frames, the main frame and roof truss. The main order forms concrete columns and beams, roof truss is made around the ground used as roof trusses as well as limiting the product dimension. Roof frame is made of iron frame. The main structure in the form of a slab of concrete as a bridge pylon built on both ends (left and right) product. The center of the flue products was made from used containers, which were mounted inside the air purifier material suckles adapt Mono cylinder chimney. GCR has exhaust fan as a puller emissions into the chimney. Cooler Roof global uses solar panels as a source of energy. The inside of the chimney is modified into a special room treatment of emissions. At the border there is a maze arrangement forming successive layers of coconut fiber, sponge, and activated carbon. Coconut fiber serves to filter out larger material, such as dust, ash, and others. Spoon serves to absorb the liquid vapor. Activated carbon is very beneficial, i.e., to filter emission gases (CO2, NOx, Pb, CH4 etc.). Air and exhaust gases exit through the hole. So at the end of the clean air were out into the environment through the outlet.